Knowledge, attitude and practice of nursing and computer science students on blood donation. A comparison study - Mohamed Ariffin, Suzilawati; Mohd Raf, Nur Syahirah; Aung, Khin Thandar (IOSR Journal of Nursing and Health Science (IOSR-JNHS), 2017)
Saving lives could be a noble act and donating blood is one way to do it. People can save up to three lives by donating blood because a pint of blood actually can be separated into three components which are red blood cells, platelets and plasma. In order to increase blood supply and to maintain adequate stock of blood, voluntary and regular blood donors are needed to meet the increasing demand. The donation from young adults like university students is more preferable because they are a healthy group with a low risk of transmitting disease and more knowledgeable than the other groups. Considering the significance of university students in blood donation practice, the aim of the study was to assess university students’ knowledge, attitude and practice on blood donation among nursing and computational sciences students. Methods/Materials: A descriptive cross-sectional study was conducted on 295 students from nursing and computational science programs. A well-structured questionnaire was used as research instruments which is adapted from Amatya (2012) with the author’s permission and internal reliability was Cronbach’s alpha >0.7 . Data was analyzed by using SPSS version 20 and then measured the association between variables using the Chi-square test. Result: There was93.6% response rate and 98% of the respondents had high knowledge and 96.6% had a positive attitude about blood donation. Among 35.6% respondents who had donated before; six were regular donors. More male respondents practiced blood donation compared to female which was 50% and 30.6% respectively. There was a significant association between year of study with blood donation attitude among respondents in IIUM (p value = 0.037).There was a significant association between year of study and practice of blood donation(p value = 0.011)There was a significant association between gender and practice (p value = 0.002).Meanwhile, gender had no association between knowledge and attitude towards blood donation. Most respondents donated for moral satisfaction and humanity while the commonest reason for not donating was restraint factors: medically unfit, time constraint, and no permission from parents. Conclusion: Organizing more blood donation campaigns and participation of students in the occasion will increase blood donation practice. The study findings can be a baseline evidence for health care professionals and may contribute to develop an educational platform on blood donation globally.